Meteorological observation at Syowa Station in 1979 by the 20th Japanese Antarctic Research Expedition - Shigemi Meshida; Koji Tsukamura; Yuji Yamamoto; Mitsuyuki Kosha (National Institute of Polar Research, 1983)
This paper describes the results of meteorological observations (mainly surface and aerological) at Syowa Station from February 1,1979 to January 31,1980. Methods and equipments for observations are the same as in 1978. The observed data were sent to World Meteorological Center at Melbourne via Mawson Station according to the WMO Regulations. Remarkable characteristics are as follows : 1) The weather remained unsettled with strong wind between autumn and the beginning of winter. Especially in April the monthly mean wind speed was 3.2 m/s higher than the normal. 2) The number of blizzards was almost the same as that of the average. But a few blizzards had lasted long. 3) Annual variation of temperature became pot-shaped, because in June and July the monthly mean temperatures were lower by 2℃ or more. 4) Stratospheric sudden warming had occurred one-month earlier. 5) Fine weather kept on one month or more from September to October and from November to December.